Prevalência e identificação de linhagens de hemoparasitas em populações brasileiras e africanas de Bulbucus ibis (Ardeidae, Pelecaniiformes, Aves) - Villar, Cynthia Martins (2013)
The cattle egret (Bubulcus ibis), native from Africa, invaded the American continent by the end of the XIX century, initiating the process of colonization through the north of South America and spreading throughout the continent. Haemoparasites are found in all continents in the world, with the exception of Antarctica, and in preliminary tests it was verified they are present in the cattle egret population. The objectives of this work were to estimate the prevalence of the haemoparasites Plasmodium and Haemoproteus on African and Brazilian populations of B. ibis and to identify the repertoire of the lineages in these populations. Blood samples and blood slides were acquired from B. ibis nestlings in six brazilian populations and in 15 african populations, located at the west coast, totalling around 859 individuals. For the molecular diagnosis, fragments of the cytochrome B gene of the Plasmodium spp. and the Haemoproteus spp. were amplified. The DNA of the parasite in the infected individuals was sequenced and the identification of the genus and the lineages present was performed through phylogenetic analysis via the bayesian method using the Mr. Bayes software. These results were partially confirmed by the morphological diagnosis. The prevalences in Africa for the Plasmodium genus decreased from Senegal and Guinea-Bissau to South Africa, while Brazilian prevalences increased from Pará to Rio Grande do Sul. The diversities of African lineages of Plasmodium spp. were higher in regions close to and above the Equator line; the highest Brazilian diversity was also found near the Equator. The G pair to pair statistical test did not reveal difference between the prevalences of African and Brazilian cattle egret populations, both for the Plasmodium and for the Haemoproteus genera. Significant difference was detected relative to the richness of the lineages of the Plasmodium genus found in Africa and Brazil, partially confirming the predictions of the Enemy Release Hypothesis. Some evidence points to African countries near and above the Equator line as African source-founder populations of the cattle egret that colonized Brazil.